2000
DOI: 10.1177/10547730022158708
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Methods of Obtaining Orthostatic Vital Signs

Abstract: The purpose of this study was to compare two lying and standing procedures for measuring orthostatic vital signs. Thirty-five normotensive participants (mean age 21.6 years)participated in a randomized crossover study. Measures of blood pressure (BP), heart rate, and dizziness were collected at different lying and standing times. AU subjects participated in a standardized walk paced at 4 miles per hour prior to lying. Using analysis of variance (ANOVA) with post hoc contrasts, the mean systolic BP differed bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Orthostatic challenges, such as position changes, are used frequently to assess a range of sympathetic and parasympathetic responses (Lance et al, 2000). Changing from a recumbent to a standing position results in a reduction of cardiac output and is counteracted by tachycardia after 10 seconds to maintain mean arterial pressure (DeBroer, Karemaker, & Strackee, 1987;Savard & Stonehouse, 1995).…”
Section: Cardiac Rate Responsementioning
confidence: 99%
“…Orthostatic challenges, such as position changes, are used frequently to assess a range of sympathetic and parasympathetic responses (Lance et al, 2000). Changing from a recumbent to a standing position results in a reduction of cardiac output and is counteracted by tachycardia after 10 seconds to maintain mean arterial pressure (DeBroer, Karemaker, & Strackee, 1987;Savard & Stonehouse, 1995).…”
Section: Cardiac Rate Responsementioning
confidence: 99%
“…2003) there is some evidence to suggest that they may be manifested earlier. The largest drops in SBP in non‐bed rest populations have been found to occur immediately (Lance et al. 2000, Youde et al.…”
Section: Discussionmentioning
confidence: 99%
“…The largest drops in SBP in non-bed rest populations have been found to occur immediately (Lance et al 2000, Youde et al 2002, at one minute (Gehrking et al 2005), and within three minutes (Gibbons & Freeman 2006) upon resuming upright posture. The largest drop in DBP has been found to occur at 45 seconds upon resuming upright standing (Maurer et al 2004); a similar time period has been identified for maximal increase in HR (Melby et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They measured vital signs following one minute, five minutes and 20 minutes of rest and found that "the augmentation of the BP and HR response is small when the period of rest is increased from five to 20 minutes, it seems adequate to perform this test after at least five minutes of supine rest" (Harkel, Lieshout, Lieshout, & Wieling, 1990, p. 152). However, Lance et al (2009) found that 10 minutes of rest was required for accurate measurement of orthostatic vital signs. It should be noted that both studies by Harkel et al and Lance et al were conducted on small samples of 10 and 34 (respectively) of young, healthy, normotensive subjects.…”
Section: Supinementioning
confidence: 98%
“…A review of definitions from the literature indicates that the assessment parameter labeled as orthostatic vital signs can be summarized by its: physiological variables, measurement method, and purpose. The physiological variables include blood pressure, heart rate, and stroke index (Durukan et al, 2009;Fuchs & Jaffe, 1987;Horam & Roscelli, 1992;KoziolMcLain et al, 1991;Levitt et al, 1992;Witting & Gallagher, 2003), as well as symptoms of dizziness or lightheadedness (Lance et al, 2009;Sarasin et al, 2002). Stated purposes of orthostatic vital signs assessment include identification of hypovolemia (both dehydration and blood loss) and treatment efficacy of pharmacological agents for neurological conditions.…”
Section: Summary Of Definitionsmentioning
confidence: 99%